Evaluasi Perencanaan Penanganan Existing Jalan yang Tidak Stabil pada Ruas Jalan Gunting Saga – Teluk Binjai Kab. Labuhan Batu Utara: Studi Kasus - Muhammad Arif Gusfimi; Marwan Lubis; Hamidun Batubara (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The Gunting Saga - Teluk Binjai Road section (North Labuhan Batu Regency) is a Collector Road or Regency Road that connects the city of Aek Kanopan and the city of Kualuh Hilir. On this section of road, several large and heavy vehicles often pass with geometric conditions that are not too wide and at some points the ground conditions are less stable, which results in poor traffic flow and also damage to parts of the road. The impact of the lack of width and damage to the existing condition of the Gunting Saga - Teluk Binjai section is: hampering economic activity in the area. The aim of the study is to plan flexible pavement and widening on road shoulders and also plan flexible pavement on additional or overlay pavement.To support this study, several data are needed, such as: traffic volume data, rainfall data, CBR data, Benkelman beam data and also unit price analysis data using secondary data obtained from the North Sumatra Province National Road Planning and Supervision Working Unit. From the results of the data obtained, it is then processed and analyzed in the calculation of flexible pavement for new roads and additional pavement (overlays) using Bina Marga standards for flexible pavement analysis using Instructions for Planning the Thickness of Flexible Pavement for Highways Using the Component Analysis Method (SKBI-2.3.26.1987), Meanwhile, for additional pavement analysis (overlay), the Hot Rolled Overlay Design For Indonesia method is used.From the calculation results, it is obtained that the thickness of the flexible pavement layer for the new road and also the thickness of the additional pavement layer (overlay) are obtained with various values, namely: segment 1 has a layer value of D1 = 5,4 cm, D2 = 25 cm, D3 = 35 cm as well as for each segment so on up to four segments.